The Three Fundamental University Missions: Brazilian Challenges - Gimenez, Ana Maria Nunes; Gavira, Muriel de Oliveira; Bonacelli, Maria Beatriz M. (International Higher Education, 2024)
<h3 id="since-the-1988-constitution-brazilian-higher-education-institutions-have-been-required-to-combine-teaching-research-and-extension-in-an-integrated-way-called-inseparability-however-progress-toward-achieving-this-integration-has-been-slow-due-to-lingering-doubts-about-what-inseparability-means-and-how-to-implement-it-we-reflect-on-the-challenges-that-must-be-overcome-to-fully-integrate-the-missions-of-brazilian-universities-institutions-in-other-countries-especially-in-the-global-south-may-face-similar-challenges" data-pm-slice="1 1 []">Since the 1988 constitution, Brazilian higher education institutions have been required to combine teaching, research, and extension in an integrated way, called inseparability. However, progress toward achieving this integration has been slow due to lingering doubts about what inseparability means and how to implement it. We reflect on the challenges that must be overcome to fully integrate the missions of Brazilian universities. Institutions in other countries, especially in the Global South, may face similar challenges.